Revision of Chlororithra Butler, 1889 (Lepidoptera, Geometridae, Geometrinae) - Han, Hongxiang; Li, Hongmei; Xue, Dayong (Zootaxa, 2006)
The genus Chlororithra Butler, 1889 is revised. Based on an examination of the syntypes of C. missioniaria Oberthür, we elevate that taxon to species status. Differences between C. fea Butler and C. missioniaria and variation within each species are discussed in detail and illustrated. A lectotype is designated for C. fea. Tribal placement of the genus is discussed.